The Ramayana in Assam of India with Reference to the Thai Ramakien - Das, Nripen Chandra (วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย, 2020)
Assam is one of the states of North East India. The Ramayana in Assamese verse written by Madhava Kandali in the fourteenth century A.D. was based on Valmiki’s Sanskrit Ramayana. This was the first Ramayana written ever in any languages of the North East India and one of the oldest Ramayanas written in provincial languages of India. The complete Ramayana consists of 7 kandas (chapters), but two kandas of Madhava Kandali’s Ramayana could not be recovered. So the Assamese Ramayana of Madhava Kandali was later on completed by Uttarakanda and Adikanda written by medieval Vaishnava saints Sankardeva and Madhavadeva respectively. There are two more Ramayanas in Assamese: Durgabari Ramayana (musical Ramayana) and Kathaa Ramayana (prose Ramayana). Ananta Kandali wrote the Bhakti Ramayana. But it is a fact that in Assam Ramayana tradition as a whole is older than the Ramayana in written form. So the tradition literary as well as folk has been continuing in the state uninterruptedly. The influence of the Ramayana is found in all aspects of the Assamese society. Among the tribal people of the state also Ramayana legends are prevalent in written as well as oral tradition. Comparatively the impact of the Ramayana on Thailand in a remarkable way is a phenomenon of eighteenth century A.D. In folk performing art and life this influence on both the lands is very profound and this is the main aspect emphasized in this paper.